Suppressing the Substance P-NK1R Signalling Protects Mice against Sepsis-Associated Acute Inflammatory Injury and Ferroptosis in the Liver and Lungs - Zhixing Zhu; Stephen Chambers; Madhav Bhatia (MDPI AG, 2024)
Substance P (SP), encoded by the TAC1/Tac1 gene, acts as a significant mediator in dysregulated systemic inflammatory response and associated organ injury in sepsis by activating the neurokinin-1 receptor (NK1R). This study investigated the impact of SP-NK1R signaling on ferroptosis in the liver and lungs of mice with sepsis. Sepsis was induced by caecal ligation puncture (CLP) surgery in mice. The SP-NK1R signaling was suppressed by Tac1 gene deletion, NK1R blockade, and a combination of these two approaches. The physiological conditions of mice were recorded. The profile of the SP-NK1R cascade, inflammatory response, ferroptosis, and tissue histology were investigated in the liver and lungs. Several manifestations of sepsis occurred in Tac1+/+ mice during the development of sepsis. Notably, hypothermia became significant four hours after the induction of sepsis. In the liver and lungs of mice subjected to CLP surgery, the concentrations of SP and NK1R were upregulated. Additionally, the concentrations of pro-inflammatory mediators, including cytokines (IL-1β, IL-6, and TNF-α) and chemokines (MCP-1 and MIP-2), were increased. Moreover, ferroptosis was elevated, as evidenced by increased concentrations of iron and MDA and reduced concentrations of GSH, Nrf2, and Gpx4. Suppressing the SP-NK1R cascade significantly mitigated CLP-surgery-induced alterations in mice. Importantly, these three approaches used to suppress SP-NK1R signaling showed similar effects on protecting mice against sepsis. In conclusion, increased SP-mediated acute inflammatory response and injury in the liver and lungs in mice with CLP-surgery-induced sepsis was associated with elevated ferroptosis. The detrimental effect of SP on sepsis was predominantly mediated by NK1R. Therefore, the suppression of increased SP-NK1R signaling and ferroptosis may be a promising adjuvant therapeutic candidate for sepsis and associated acute liver and lung injury.